Fatores associados ao uso de medicamentos potencialmente inapropriados em idosos urbanos e rurais - Salcher, Eduarda Brum Guedes (2017)
A dominant property of an elderly population is the presence of chronic disease. Regarding to this condition, the therapeutic treatment of aged people is basically through the pharmacologic treatment. The usage of potentially inappropriate medicines (PIM) by elderly people becomes an uncongenial factor. The main objective of this study was to identify associations among the usage of PIM by elderly people living in urban and rural areas and their residency area, health conditions, habits and functional capacity. This was a transversal study, which belongs to a population based study that analyzed habits and health conditions of elderly populations from urban and rural areas of Estação – RS. The studied population was composed by individuals residing in urban and rural areas of that city, only 60 years old or older were included in this study. The data was collected using inquiries on their own household. The following subjects were considered: A) Personal and family information, D) Health and habit conditions, and, E) Functional evaluation. The collected information was codified and stored on a database. After the self-referenced medicines, it was selected the elderly people that uses medicines, compounding the final study population of 313 people. The self-referenced medicines were classified following Beers’s Criteria, version 2012. The results were compiled as a scientific production entitled as "Associated factors to potentially inappropriate medicines usage by elderly people from urban and rural areas.", which aimed to verify associations between the PIM usage and the residency area. It was identified a positive association between the PIM usage and pain, falls, athletics, diabetes, sleep problems, nervousness, cardiac problems,depression and basic daily activities. The study demonstrated an elevated prevalence by the usage of PIM by elderly people while at a community. Generally, by the end of the project, it can be concluded that PIM usage is elevated by elderly people living both in urban and rural areas, the repercussion of this reality can strongly influence health conditions of elderly people. So, it must be encouraged the awareness of the multi-professional team for the coherent and regulated usage of medicines in this kind of population, minimizing risks and damages to their health conditions. This research was approved by the Ethics Committee of Research from the .University of Passo Fundo under the number 017/2011. The data gathering followed recommender guidelines under the Resolution 466/12 from the National Health Council